Human Endometrial Organoids: Recent Research Progress and Potential Applications - Lou, Liqun; Kong, Shuangbo; Sun, Yunyan; Zhang, Zhenbo; Wang, Haibin (Frontiers in Cell and Developmental Biology, 2022)
Since traditional two-dimensional (2D) cell culture cannot meet the demand of simulating physiological conditions in vivo, three-dimensional (3D) culture systems have been developed. To date, most of these systems have been applied for the culture of gastrointestinal and neural tissue. As for the female reproductive system, the culture of endometrial and oviductal tissues in Matrigel has also been performed, but there are still some problems that remain unsolved. This review highlights recent progress regarding endometrial organoids, focusing on the signal for organoid derivation and maintenance, the coculture of the epithelium and stroma, the drug screening using organoids from cancer patients, and provides a potential guideline for genome editing in endometrial organoids.